Kolaborasi Gonjong Limo” di Gugus Depan 019-020 Pangkalan SDN 04 Payakumbuh - Wira Hayu (Departement of Mathematics Education, 2022)
The phenomenon that occurs in the Front Group 019-020 SDN 04 Payakumbuh is that scouting education has not been implemented optimally in the 2013 curriculum, and the difficulty of achieving front group achievements let alone maintaining the achievements that have been achieved. There are no programs that are planned and implemented on an ongoing basis in the context of coaching and empowering existing resources in the front group. The low achievement of students and institutions in the front group affects success, the achievements in question are SKU, SKK and achievements in competitions. Students are coached by certain coaches only, from male and female units, not all educators, while scouting education must be taught which of course all teachers must play a role. The effort taken to overcome this problem is the Gonjong Limo Collaboration. Namely mutual cooperation movement to advance the achievements and achievements together of both students and group coaches in the Front Gugus 019-020 SDN 04 Payakumbuh, with the following programs: (1) Gonjong Ciek Program; administration and management. (2) Gonjong Duo Program; activities (3) Gonjong Tigo Program; process (4) Gonjong Ampek Program; best practice. (5) Gonjong Limo Program. The benefits of these programs are to maximize the implementation of scouting education in the 2013 curriculum and can have a positive and significant impact on the front group 019-020 SD N 04 Payakumbuh in the form of good achievements at the regional and national levels, excellence, and models for other front gigs.